2009
DOI: 10.1007/s11120-009-9497-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylglycerol depletion affects photosystem II activity in Synechococcus sp. PCC 7942 cells

Abstract: The role of phosphatidylglycerol (PG) in photosynthetic membranes of cyanobacteria was analyzed in a Synechococcus sp. PCC 7942 mutant produced by inactivating its cdsA gene presumably encoding cytidine 5'-diphosphate-diacylglycerol synthase, a key enzyme in PG synthesis. In a medium supplemented with PG the Synechococcus sp. PCC 7942/DeltacdsA cells grew photoautotrophically. Depletion of PG in the medium resulted (a) in an arrest of cell growth and division, (b) in a suppression of O(2) evolving activity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…It indicates that the essential pool of PG is very small. In agreement with previous reports (Gombos et al, 2002;Bogos et al, 2010;Itoh et al, 2012), PG starvation triggered a decrease in Chl content; the loss of Chl per cell was already apparent after 48 h followed by a gradual decrease to approximately 50% of the original Chl level after 5 d ( Fig. 1; Table I).…”
Section: Pg Depletion Results In Inhibition Of De Novo Chl Biosynthessupporting
confidence: 93%
“…It indicates that the essential pool of PG is very small. In agreement with previous reports (Gombos et al, 2002;Bogos et al, 2010;Itoh et al, 2012), PG starvation triggered a decrease in Chl content; the loss of Chl per cell was already apparent after 48 h followed by a gradual decrease to approximately 50% of the original Chl level after 5 d ( Fig. 1; Table I).…”
Section: Pg Depletion Results In Inhibition Of De Novo Chl Biosynthessupporting
confidence: 93%
“…PCC 6803 and Synechococcus sp. PCC 7942, a number of mutant studies have demonstrated that PG is physiologically essential and is notably involved in the activity of both photosystems, influencing the dimerization and reactivation of core complexes (Sakurai et al, 2003;Bogos et al, 2010;Yamamoto, 2016). X-ray crystallographic analysis of photosystem II at 1.9 Å resolution has identified 5 PG molecules bound to photosystem II, directly connected to the D1 protein and plastoquinone Q B (Itoh et al, 2012;Mizusawa and Wada, 2012).…”
Section: Cold-induced Desaturations Of Acyl Chains In Synechococcus Smentioning
confidence: 99%
“…However, Synechococcus sp. PCC 7942 has been regarded as an obligate photoautotroph (Kratz and Myers 1955;Zhang et al 1998), and many studies have been done in photoautotrophic cultures (e.g., Tsinoremas et al 1994;Sauer et al 2001;Bogos et al 2010). Despite of that, there have been studies which suggest that some obligate photoautotrophic cyanobacteria can assimilate organic carbon sources (Hoare et al 1967;Pelroy et al 1972;Pearce and Carr 1967;Khoja and Whitton 1971).…”
Section: Introductionmentioning
confidence: 99%